Electronic scoring system - algorithm for microcontroller unit - Vrachkov, Dimitar Georgiev; Todorov, Dimitar Georgiev (2017 XXVI International Scientific Conference Electronics (ET), 2017)
This report examines a system for electronic measurement and calculation of the coordinates of an object on a target and subsequent reporting of a certain result on the position of the object. It is a method of locating objects using sound receivers - TDOA (Time Difference of Arrival), a part of multilateration (MLAT) method used to locate mobile phones, civil aviation aircraft, locating military objects, and more. Also is presented a lightweight algorithm for calculating coordinates of the localized object based on measured times by sound sensors. An overview of the problems to be overcome is made. Suggestions for decisions were made allowing the implementation of the system into a real embedded project. A scheme for implementing the system has been proposed. The limitations of the measurement method in terms of practical implementation are defined and some ideas are outlined to minimize these limitations. The application of such systems is a training and training purpose, sports shooting equipment, applicable to other games using targets and requiring electronic reporting of the result.